A review on zinc oxide composites for energy storage applications: solar cells, batteries, and supercapacitors - Hoang Bui, Vu Khac; Kumar, M. Krishna; Alinaghibeigi, Mahdi; Moolayadukkam, Sreejesh; Eskandarinejad, Sara; Mahmoudi, Shirin; Mirzamohammadi, Sadegh; Rezaei-khamseh, Mojdeh (Journal of Composites and Compounds, 2021)
Zinc oxide (ZnO) is used for various purposes because of its special physico-chemical properties, including large band gap, high binding energy of exciton, nontoxicity, high chemical and thermal stability, large piezoelectric constants, and wurtzite crystal structure with various and widespread applications in electronics, optoelectronics, biochemical sensing, biomedical, and energy-saving systems. This review mainly aimed to present the recent improvement in ZnO-based composite materials with utilization in energy storage systems with a specific focus on lithium-ion batteries, dye-sensitized solar cells, and supercapacitors. The first part of this paper looks at the structure and properties of ZnO and then describes some of the most common synthesizing methods of ZnO composites, including electrochemical, chemical, solvo/hydrothermal, and physical deposition methods. Finally, the recent advancement of ZnO-based composite materials applied in energy storage systems was discussed.